Rotating Machineries Aspects of Operation and Maintenance - Sulaiman, Shaharin Anwar (SpringerBriefs in Applied Sciences and Technology,, 2019)
This book discusses the maintenance aspect of rotating machines, which it addresses through a collection of contributions. Sharing the "hands-on" views of experienced engineers on the aspect of maintenance for rotating machines, it offers a valuable reference guide for practicing engineers in the related industries, providing them a glimpse of some of the most common problems associated with rotating machines and equipment in the field, and helping them achieve maximum performance efficiency and high machine availability.